2010
DOI: 10.1021/nn100748k
|View full text |Cite
|
Sign up to set email alerts
|

Size-Dependent Reactivity of Diamond Nanoparticles

Abstract: Photonic active diamond nanoparticles attract increasing attention from a wide community for applications in drug delivery and monitoring experiments as they do not bleach or blink over extended periods of time. To be utilized, the size of these diamond nanoparticles needs to be around 4 nm. Cluster formation is therefore the major problem. In this paper we introduce a new technique to modify the surface of particles with hydrogen, which prevents cluster formation in buffer solution and which is a perfect star… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
282
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 359 publications
(314 citation statements)
references
References 26 publications
15
282
0
1
Order By: Relevance
“…24,25 In conclusion, we propose a physically consistent way of interpreting Raman spectra of nanoparticles. Since the 3D dispersion function takes into account the anisotropy of the phonon dispersion, the model built in this way has a straightforward physical meaning.…”
mentioning
confidence: 86%
“…24,25 In conclusion, we propose a physically consistent way of interpreting Raman spectra of nanoparticles. Since the 3D dispersion function takes into account the anisotropy of the phonon dispersion, the model built in this way has a straightforward physical meaning.…”
mentioning
confidence: 86%
“…Such diamond nanoparticles were prepared by milling [7][8][9] and before long by purification techniques [10,11] from agglomerates about 100 nm in size. Then, solid composite was produced from 4 nm particles by sintering at high pressure and high temperature (HPHT).…”
Section: Introductionmentioning
confidence: 99%
“…For example, it has been reported that 5 nm diamond nanoparticles could be manipulated into nodal patterns using acoustic standing waves field 24. However, driving by the high surface energy, the diamond nanoparticles with ultra‐small size are particularly known to form large agglomerates 39, 40, 41. As the nanoparticles in the experiments were not treated with a surfactant to prevent the self‐assembly, the actual manipulation effect may depend on the size of agglomerates rather than that of single nanoparticle.…”
Section: Discussionmentioning
confidence: 99%